Co-administration of temozolomide (TMZ) and the experimental therapeutic targeting miR-10b, profoundly affects the tumorigenic phenotype of human glioblastoma cells - Chen, Ming; Kim, Bryan; Robertson, Neil; Mondal, Sujan Kumar; Medarova, Zdravka; Moore, Anna (Frontiers in Molecular Biosciences, 2023)
Recent studies have shown that miRNA-10b is highly expressed in high-grade glioblastoma multiforme (GBM), and its inhibition leads to deregulation of multiple pathways in tumorigenesis, resulting in repression of tumor growth and increased apoptosis. Thus, we hypothesized that suppressing miR-10b could enhance the cytotoxicity of conventional GBM chemotherapy with temozolomide (TMZ). Inhibition of miR-10b in glioblastoma cells was achieved using an experimental therapeutic consisting of anti-miR10b antagomirs conjugated to iron oxide nanoparticles (termed MN-anti-miR10b). The nanoparticles serve as delivery vehicles for the antagomirs as well as imaging reporters guiding the delivery in future animal studies. Treatment of U251 and LN229 human glioblastoma cells with MN-anti-miR10b led to inhibition of miR-10b accompanied by repression of growth and increase in apoptosis. We next explored whether MN-anti-miR10b could enhance the cytotoxic effect of TMZ. During these studies, we unexpectedly found that TMZ monotherapy increased miR-10b expression and change the expression of corresponding miR-10b targets. This discovery led to the design of a sequence-dependent combination treatment, in which miR-10b inhibition and induction of apoptosis by MN-anti-miR10b was followed by a sub-therapeutic dose of TMZ, which caused cell cycle arrest and ultimately cell death. This combination was highly successful in significant enhancement of apoptosis and decrease in cell migration and invasiveness. Considering the unexpected effects of TMZ on miR-10b expression and possible implications on its clinical application, we reasoned that comprehensive in vitro studies were warranted before embarking on studies in animals. These intriguing findings serve as a solid foundation for future in vivo studies and offer promise for the successful treatment of GBM.